2015
DOI: 10.1021/acsami.5b00915
|View full text |Cite
|
Sign up to set email alerts
|

Design of LVFFARK and LVFFARK-Functionalized Nanoparticles for Inhibiting Amyloid β-Protein Fibrillation and Cytotoxicity

Abstract: Aggregation of amyloid β-protein (Aβ) into amyloid oligomers and fibrils is pathologically linked to Alzheimer's disease (AD). Hence, the inhibition of Aβ aggregation is essential for the prevention and treatment of AD, but the development of potent agents capable of inhibiting Aβ fibrillogenesis has posed significant challenges. Herein, we designed Ac-LVFFARK-NH2 (LK7) by incorporating two positively charged residues, R and K, into the central hydrophobic fragment of Aβ17-21 (LVFFA) and examined its inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 69 publications
10
147
0
Order By: Relevance
“…Moreover, similar results have also been found in previous studies. 13,31,64 Thus it can be concluded that brazilin prevents the amyloidogenesis of hIAPP and leads to the generation of short rod-like aggregates.…”
Section: Brazilin Inhibits Hiapp Brillogenesismentioning
confidence: 99%
“…Moreover, similar results have also been found in previous studies. 13,31,64 Thus it can be concluded that brazilin prevents the amyloidogenesis of hIAPP and leads to the generation of short rod-like aggregates.…”
Section: Brazilin Inhibits Hiapp Brillogenesismentioning
confidence: 99%
“…Such surface modifications facilitate binding specificity and affinity between NPs and Aβ, and help to remedy the biochemical properties of the conjugated molecules. Our previous work on peptide‐functionalized poly (lactic‐co‐glycolic acid) NPs demonstrated that upon conjugation with NPs, the cell toxicity of peptide inhibitors (LVFFARK) was eliminated and inhibition efficiency was significantly enhanced . Among various NPs, gold nanoparticles (AuNPs) have attracted substantial attention because of their low cytotoxicity, unique optical properties suitable for detection/imaging, well‐established synthesis methods, and the potential capability to cross the blood brain barrier by coupling various shuttle peptides .…”
Section: Introductionmentioning
confidence: 99%
“…LK7 was detected to inhibit Aβ42 fibrillogenesis in a concentration-dependent system. However, LK7@PLGA-NPs demonstrated dramatic inhibitory effect against Aβ42 aggregation [100]. It was also revealed that the fibril fibrillation can be retarded by inhibiting the nucleation and extension phases with a low concentration of functionalized quantum dots.…”
Section: Surface Chemistrymentioning
confidence: 99%